Teacher educator and student teacher perceptions of autonomous support and practice in a faculty of education in North Cyprus - Basri, Fatma (2020)
Learner autonomy has been a popular topic of discussion and research with its potential to help learners manage their learning through taking charge of the process. It has also long been debated that teacher support for learner autonomy is a predictor of increased autonomous behaviours learners display in their learning. This study examines the perceptions of teacher educators about their conceptualisations of and support for autonomy, and the perceptions of student teachers about their conceptualisations of and practice of autonomy in their actual learning process. The study also looks at the factors that influence both teacher support and students’ development and implementation of autonomy. This study was carried out in the Faculty of Education in a university in North Cyprus. The research design utilised case study within a qualitative paradigm with semi-structured interviews and student/teacher diaries as the data collection methods to explore autonomy support and practice in a natural setting with in-depth data. Content analysis was used for the analysis of the data. Data from 15 teacher educators and 27 student teachers indicate that teacher educators support and student teachers practise learner autonomy in relation to five main categories: Metacognition, an Atmosphere Conducive to Learner Autonomy, Learner Training, Interdependence and Affect. According to both teacher educators and student teachers, there are serious barriers that hinder teacher educators’ support and inhibit student teachers’ practice. Conceptualisations and background of teachers and learners regarding autonomy, education system and teacher autonomy were reported to be the main barriers.